THE INSIDENCE OF BLADDER SQUAMOUS CELL CARCINOMA IN LARGE BLADDER STONE CASES - Pitoyo, Joko; Safriadi, Ferry (Indonesian Urological Association, 2015)
Objective: To determine the incidence of squamous cell carcinoma (SCC) in patients with large bladder stone (> 40 mm). Material & method: This is a descriptive retrospective cross-sectional study, data was collected from medical record on patients with a diagnosis of large bladder stone (> 40 mm) that have been performed surgical removal of stone (vesicolithotomy) and bladder mucosa biopsy in Hasan Sadikin Hospital Bandung during 2006-2010. Furthermore, the data are classified according to pathology. Results: This study found cases of large bladder stone (> 40 mm) of 47 cases during the period 2006-2010, and of these 47 cases, there were 76.7% and 23.3% non-malignancy of a malignancy in 2 cases (4.3%) with anatomical pathology picture of SCC. Based on the age group of patients aged 31-40 years obtained 25.5%, 41-50 years 21.3%, 51-60 years 21.3% and > 60 years 23.4%, whereas for ages below 30 years 8.5%. Based on sex, male 95.7% and 4.3% of women. Based on the size, found a stone the size of 40 mm (48.9%), stone size of 50 mm (10.6%), stone size 60 mm and 70 mm respectively (8.5%), stone size 80 mm (12.8%), stone size > 80 mm (4.3%) and 6.4% with multiple bladder stones. Conclusion: There were only two cases of bladder SCC from 47 cases patients with large bladder stone (> 40 mm) in Hasan Sadikin Hospital Bandung during 2006-2010. Keywords: Bladder Stone, bladder carcinoma, squamous cell carcinoma.